Model komunikasi pemasaran digital untuk promosi produk UMKM via Sibakul Jogja - Aisyah, Alfiyani; Lestari, Puji; Sosiawan, Edwi Arif (Program Studi Ilmu Komunikasi UII, 2025)
The COVID-19 pandemic has had a significant impact on various sectors, particularly the economy. As the backbone of Indonesia’s economy, Micro, Small, and Medium Enterprises (UMKM) faced serious challenges due to restrictions on face-to-face activities. Many business actors were forced to adapt to uncertain conditions, with digital media becoming a strategic tool for marketing. This study aims to identify and analyze the digital marketing communication models implemented by SiBakul Jogja as an innovation to support UMKM during the pandemic. A qualitative approach was employed, using in-depth interviews with UMKM actors and content analysis of the SiBakul Jogja platform. The findings show that SiBakul Jogja effectively promotes UMKM products through three models: Paid Media, paid advertisements; Earned Media, viral content that expands market reach; and Owned Media, social media management to build brand identity. These findings highlight the importance of adaptive digital communication strategies for UMKM sustainability